The factors that affecting the awareness towards zakat income among employees in Dungun / Norazhana Abd Ghani - Abd Ghani, Norazhana (2013)
Zakat is one of the pillars in Islam and a part of the ibadah for Muslims. It has been identified as an important source of financial seed to jumpstart the economy of the Muslim community and gives an impact on socio-economic development of nation. Basically, there are many types of zakat and one of them is zakat income. Zakat income is a zakat that imposed to the income of individual who are exceeds the nisab. It is not imposed towards the individual wealth but on income. It is already classified as the wealth that needs to be impose the zakat by Majlis Fatwa Kebangsaan Malaysia, 1997. The question is did employees in Dungun aware regarding zakat income? Past research was been carried out in order to investigate the level on awareness on zakat income and this research is to know the factors that affected their awareness on zakat income. The reason is the factors identified will be developed and zakat institution needs will come out with the large effort in order to improve and increase the awareness on zakat income among employees in Dungun. Several variables have been used in order to analyze either those factors are having a relationship with the awareness on zakat income. The result that came out shows that promotion strategy is the most significant variable in influencing awareness on zakat income among employees in Dungun.